Manipulation of Human Verticality Using High-Definition Transcranial Direct Current Stimulation - Santos, Taiza E. G.; Favoretto, Diandra B.; Toostani, Iman Ghodratti; Nascimento, Diego C.; Rimoli, Brunna P.; Bergonzoni, Eduardo; Lemos, Tenysson Will; Truong, Dennis Q.; Delbem, Alexandre C. B.; Makkiabadi, Bahador; Moraes, Renato; Louzada, Francisco; et al. (Frontiers in Neurology, 2018)
Background: Using conventional tDCS over the temporo-parietal junction (TPJ) we previously reported that it is possible to manipulate subjective visual vertical (SVV) and postural control. We also demonstrated that high-definition tDCS (HD-tDCS) can achieve substantially greater cortical stimulation focality than conventional tDCS. However, it is critical to establish dose-response effects using well-defined protocols with relevance to clinically meaningful applications. Objective: To present the feasibility, safety, tolerability and the pilot results of three randomized, double-blind, crossover phase I clinical trials for polarity and intensity-dependent effects of HD-tDCS over the right TPJ in behavioral and physiological outcome measures in healthy subjects. Methods: We conducted three separate clinical trials in healthy adults using the same stimulation protocol, with SVV, weight-bearing asymmetry (WBA), and electroencephalography (EEG) as outcome measures. The HD-tDCS montage comprised a single central, and 3 surround electrodes (HD-tDCS3x1) over the right TPJ. For each study, we tested 3x2min HD-tDCS3x1 at 1, 2 and 3mA; with anode center, cathode center, or sham stimulation, in random order across days. Results: We found significant SVV deviation relative to baseline, specific to the cathode center condition, with consistent direction and increasing with stimulation intensity. We further showed WBA with direction governed by stimulation polarity (cathode center, left asymmetry; anode center, right asymmetry). EEG power spectral density in the gamma band was significantly increased at 3mA under the cathode. Conclusions: The present series of studies indicates converging evidence for focal neuromodulation that can modify local and network physiology and have behavioral consequences with clinical relevance.